2020
DOI: 10.1371/journal.pgen.1008604
|View full text |Cite
|
Sign up to set email alerts
|

Murine cytomegalovirus infection exacerbates complex IV deficiency in a model of mitochondrial disease

Abstract: The influence of environmental insults on the onset and progression of mitochondrial diseases is unknown. To evaluate the effects of infection on mitochondrial disease we used a mouse model of Leigh Syndrome, where a missense mutation in the Taco1 gene results in the loss of the translation activator of cytochrome c oxidase subunit I (TACO1) protein. The mutation leads to an isolated complex IV deficiency that mimics the disease pathology observed in human patients with TACO1 mutations. We infected Taco1 mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…in our previous study, myocyte damage alongside decreased ca 2+ /Mg 2+ -aTP and na + /K + -aTP enzyme activity were observed in the skeletal muscle of eaMG rats, indicative of abnormal energy metabolism in the skeletal muscle of eaMG rats, resulting in impaired muscle diastolic movement (19). coX, also known as mitochondrial respiratory chain complex iV, is one of the oxidases essential for mitochondrial respiratory function (74). Previous studies have shown that defects in the mitochondrial respiratory chain are important factors that interfere with cellular energy metabolism and are an important cause of skeletal muscle injury (75)(76)(77).…”
Section: Discussionmentioning
confidence: 84%
“…in our previous study, myocyte damage alongside decreased ca 2+ /Mg 2+ -aTP and na + /K + -aTP enzyme activity were observed in the skeletal muscle of eaMG rats, indicative of abnormal energy metabolism in the skeletal muscle of eaMG rats, resulting in impaired muscle diastolic movement (19). coX, also known as mitochondrial respiratory chain complex iV, is one of the oxidases essential for mitochondrial respiratory function (74). Previous studies have shown that defects in the mitochondrial respiratory chain are important factors that interfere with cellular energy metabolism and are an important cause of skeletal muscle injury (75)(76)(77).…”
Section: Discussionmentioning
confidence: 84%
“…For example, the mitochondrial protein UQCC2 and its binding partner UQCC1, which both were downregulated at 1 week, are required for maintaining the mitochondrial complex ( 40 ). Mitochondrial dysfunction has been described in various severe and chronic disorders ( 40 42 ). The mitochondrial inhibition was relieved at the later stages of infection at 8 to 28 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenic variants in the TACO1 gene that encodes a translational activator of cytochrome c oxidase 1 ( MT-CO1 ) mRNA, led to late-onset Leigh syndrome, also caused by a specific Complex IV deficiency [ 79 , 80 ]. When modeled in mice, a Taco1 mutation that resulted in TACO1 loss caused similar late-onset pathologies affecting vision, motor function and learning capacity [ 81 ] that could be further exacerbated by infection mimicking sudden triggers of mitochondrial diseases [ 82 ]. TACO1 was shown to bind the MT-CO1 mRNA to facilitate its association with the ribosome and its loss caused an isolated Complex IV deficiency, consistent with the role of COXI in the initial assembly of Complex IV [ 81 ].…”
Section: Modeling the Role Of Mitochondrial Rna Regulators In Diseasementioning
confidence: 99%